A STUDY OF THE STUDENTS’ PARTICIPATION MOTIVE IN HIGH SCHOOL SPORTS CLUB: Received: 08th October 2021; Revised: 25th February 2022, 4th March 2022; Accepted: 07th March 2022 - Chang, Sheng Yuan (PUPIL: International Journal of Teaching, Education and Learning, 2022)
The purpose of this study was to explore students’ participation motive in High school sports clubs in a qualitative research manner. The research participants included 15 High school students who joined the sports club. The research was performed using conducting one-to-one deep interviews through semi-structured questionnaires. The interview data were analyzed in combination with field notes and focus group interview data to construct a mental process of the High school students in joining the sports club by utilization of a grounded theory approach. The results showed that: there were four high-order topics of the students for joining the sports clubs, namely Self-Demand, Social Support, Interpersonal Interaction and Self-Actualization. The Self-Demand contains four low-order topics; interest, pressure resistance promotion, physical fitness promotion and focused promotion. Social Support contains three low-order topics; peer influence, family support and teacher support. Interpersonal Interaction contains two low-order topics; cooperation and respect. Finally, Self-Actualization contains two low-order topics; the inspiration of potency and sense of accomplishment. It was concluded that the High school students joined the sports club due to meeting the self-demand, being influenced by the social support, suffering from the interpersonal interaction with good learning students, and inspiring the possibility of self-actualization.